Finden statt suchen: Marken an der Internet-Pinnwand. Lässt sich die Sichtbarkeit in Suchmaschinen durch gezieltes Pinterest-Marketing beeinflussen? - Desiree Schweitzer; Florian Botzenhardt; Hans-Michael Ferdinand (Markenbrand, 2015)
– Search engines like Google have a large influence on the visibility and the number of visits of e-commerce websites. A website's position within the ranking of a search engine is determined by complex algorithms. Typically, the exact operations that are being processed are not known to the public and a subject to frequent changes. E-commerce companies need to constantly improve their search engine ranking to ensure maximum visibility for potential customers. One of the impact factors are activities on social media. This study analyses the influence of marketing activities on the social network Pinterest on search engine rankings. After an experimental evaluation of the German online travel agent "hrs.de", a direct influence on the ranking through the company's efforts on Pinterest was neither confirmable nor deniable. While it is very likely that social media activities do have a positive effect on search engine optimization, the exact amount is very difficult to measure due to the nontransparent search engine algorithms.
Keywords: 650